2012
DOI: 10.1007/s00402-012-1524-5
|View full text |Cite
|
Sign up to set email alerts
|

Cementless short stem hip arthroplasty METHA® as an encouraging option in adults with osteonecrosis of the femoral head

Abstract: The study confirms encouraging results as well as good bone ingrowth of the cementless short stem arthroplasty METHA(®) even in patients with osteonecrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 31 publications
5
51
1
4
Order By: Relevance
“…Based on their results, they concluded that the Mayo Ò conservative hip is an alternative for operative treatment of ONFH. These results can be confirmed by clinical and radiological follow-up after implantation of the METHA short stem [51]. The outcome of the METHA Ò short-stem arthroplasty in 74 hips of 64 patients with ONFH showed an increase of the HHS from 37.7 preoperatively to 89.3 points after a mean follow-up of 34 months.…”
Section: Minor Bone Quality In the Femoral Neck In Onfh?supporting
confidence: 76%
“…Based on their results, they concluded that the Mayo Ò conservative hip is an alternative for operative treatment of ONFH. These results can be confirmed by clinical and radiological follow-up after implantation of the METHA short stem [51]. The outcome of the METHA Ò short-stem arthroplasty in 74 hips of 64 patients with ONFH showed an increase of the HHS from 37.7 preoperatively to 89.3 points after a mean follow-up of 34 months.…”
Section: Minor Bone Quality In the Femoral Neck In Onfh?supporting
confidence: 76%
“…Once irreversible collapse of the articular surface has taken place, according to the existing literature, attempts to preserve the femoral head are less successful and better results are achieved through joint-replacing techniques [1, 1012]. Common joint-replacement treatments include hip resurfacing, total hip arthroplasty (THA) and short stem THA [1318]. High failure and complications rates have been reported for both hemi-resurfacing and total hip resurfacing [10, 13, 19, 20], therefore total hip resurfacing is now considered a valuable option only for restricted indications [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…5 The mid-term outcome of THA using a short stem has been excellent. 2,3,[6][7][8][9] Restoration of the hip anatomy (such as femoral offset and leg length) after THA leads to improved functional outcome. 10 Restoration of the femoral offset (the distance from the centre of the femoral head to the line bisecting the long axis of the femur) improves hip abductor strength11 and range of motion, 11,12 and decreases limping, 13 dislocation risk, 14 cup strain, and polyethylene wear.…”
Section: Introductionmentioning
confidence: 99%